2001
DOI: 10.1021/jf001460e
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Protein Structure and Gelling Properties in Dried Egg White Products

Abstract: The relationship between protein structure and aggregation, as well as heat-induced gelling properties, of seven dried egg white (DEW) products was investigated. Strong correlations were found between average molecular weight and hydrophobicity plus surface SH groups of DEW-soluble protein aggregate (SPA). This suggests that hydrophobic interactions and disulfide bond formation between protein molecules were involved in the aggregation. The average molecular weight of DEW products with alkaline pHs was relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 22 publications
(29 reference statements)
2
32
0
1
Order By: Relevance
“…The stiffest gels were obtained when the denaturation temperature, the surface hydrophobicity and the ellipticity of the protein was high, whereas, measurements at 295 nm (fluorescence intensity, maximal emission wavelength, absorbance variation in CD) were low. Parts of these results are in agreement with the literature since Handa et al (2001) showed that gel firmness increased with protein surface hydrophobicity. On the opposite, Kato, Ibrahim, Watanabe, Honma, and Kobayashi (1990) showed that gel firmness increased with the decrease of denaturation temperature and ellipticity of egg white proteins, but they were working on single protein solutions and not with egg white, as in the present study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The stiffest gels were obtained when the denaturation temperature, the surface hydrophobicity and the ellipticity of the protein was high, whereas, measurements at 295 nm (fluorescence intensity, maximal emission wavelength, absorbance variation in CD) were low. Parts of these results are in agreement with the literature since Handa et al (2001) showed that gel firmness increased with protein surface hydrophobicity. On the opposite, Kato, Ibrahim, Watanabe, Honma, and Kobayashi (1990) showed that gel firmness increased with the decrease of denaturation temperature and ellipticity of egg white proteins, but they were working on single protein solutions and not with egg white, as in the present study.…”
Section: Resultssupporting
confidence: 92%
“…Heating of egg white powder at 75-80°C for 10-15 days is widely used in industry to offset functional property losses resulting from the spray-drying process: both gelling and foaming properties improve after such a dry-heating treatment (Handa, Hayashi, Shidara, & Kuroda, 2001;Kato, Ibrahim, Watanabe, Honma, & Kobayashi, 1989;Mine, 1996). However, it would be interesting to identify the critical steps of the drying process, to understand the mechanisms responsible for the functional property losses in order to limit their harmful effects, and thus to reduce storage time at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1b, higher atomization pressure and outlet air temperature provide to a certain improvement in gelling properties. In general, surface hydrophobicity increases during drying of egg and has a beneficial effect on the gel texture (Kato et al 1990;Handa et al 2001;Baron et al 2003). It was found that the gel texture was not affected significantly by the air inlet temperature ( Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…The N-terminal protein is acetylated and contains four cysteine and one cysteine residue [36]. Hydrophobic interactions and disulfide bond formation between ovalbumin molecules is involved in aggregation and surface gelatinization [37]. This structure of ovalbumin may be responsible for the relatively large molecular weight of the grafted-PMMA branches.…”
Section: Collagensmentioning
confidence: 99%